Drugs in clinical development for multiple sclerosis: focusing on anti-CD20 antibodies. (October 2013) - Gasperini, Claudio; Haggiag, Shalom; Ruggieri, Serena
<x xml:space="preserve">Abstract</x> Introduction: Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS), traditionally considered to be an autoimmune disease. Despite the standard of care for patients with MS is significantly improved in recent years, there is still room for improvement in terms of effectiveness and also compliance. Areas covered: The continuous improvements of our understanding of the pathophysiological changes that occur in MS have translated into many novel therapeutic agents at different stages of development. A number of therapies for MS are in advanced development and likely to be available soon. Along with these, we have also seen the appearance of a group of drugs considered together as a consequence of their similar design: the monoclonal antibodies (mAbs). Here, the focus will be on reviewing results that have emerged from a better clarification of MS pathogenesis to clinical trials of different anti-CD20 mAbs. Expert opinion: The decision to switch established patients from well-known drugs to either new formulations or new agents will be made on balancing efficacy and tolerability of the existing treatments. Safety seems increasingly likely to become a key factor.